An assessment of age determination methods for captured passerine birds - (:unkn) unknown (My University, 1996)
Various methods of determining age of passerine birds, using eye color, shape of flight feathers, plumage color patterns, etc. are presented in handbooks for bird banders, such as Pyle, et al., Identification Guide to North American Passerines (1987). We compared several such methods with the standard, reliable (but time-consuming) method, "skulling", in 22 species of passerines captured and banded during Fall 1994, in a general netting operation at the University of Wisconsin-Milwaukee Field Station. In many species these methods were in agreement; however in 10 species there was substantial disagreement, especially involving buffy covert tips in thrushes and shape of rectrices or primary remiges in warblers. Since members of these groups are caught in large numbers, it is important to reevaluate these criteria and find more reliable methods.
Keywords: Passerine birds; age determination; bird banding